Kajian Feminisme Dalam Kumpulan Cerpen “Akar Pule” Karya Oka Rusmini - Hapsari, Winie Setia Prilapnita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research aims describe (1) the form of directive speech acts in the comedy soap operaSegelas Stories Keluarga Kusuma; (2) the function of directive speech acts in the comedy soap opera Segelas Stories Keluarga Kusuma; and (3) the relevance of directive speech acts in the comedy soap opera Segelas Stories Keluarga Kusuma with Indonesian language teaching materials. This research is a descriptive research. The data analysis method in this study used a qualitative descriptive method. The data used in this study is in the form of directive speech in the comedy soap opera Segelas Keluarga Kusuma's story. Data collection techniques in this study used reading and note-taking techniques. The results of this study indicate that 1) the forms of directive speech acts found in the comedy soap opera Segelas Keluarga Kusuma are news sentences, imperative sentences, interrogative sentences, and exclamations. 2) the function of directive speech acts found in the comedy soap opera Segelas Keluarga Kusuma are ordering, criticizing, suggesting, inviting, and prohibiting. 3) The relevance of directive speech acts with Indonesian language teaching materials found in the comedy soap opera Segelas Keluarga Kusuma, namely in terms of language, mental maturity (psychology), and cultural background.